COX-2 and TGF-β expression in proliferative disorders of canine prostate - Rodrigues, Marcela M.P. [UNESP]; Di Santis, Giovana W.; De Moura, Veridiana M.B.D.; Amorim, Renée Laufer [UNESP] (My University, 2010)
COX-2 and TGF-β expression was determined in order to correlate non-neoplastic lesions, preneoplastic lesions and carcinoma in the prostate of dogs. The results show that neoplastic and preneoplastic lesions express more COX-2 and TGF-β when compared to carcinomas, which suggests these proteins may cooperate in the process of prostate tumorigenesis.
Keywords: Carcinoma prostate; COX-2; Dog; Preneoplastic lesions; Tgf-β .; Canis familiaris